Wear of polyetherketoneketones — Influence of titanium dioxide content and antagonistic material. Issue 3 (March 2018) - Kewekordes, Thomas; Wille, Sebastian; Kern, Matthias
Abstract: Objective: The aim of this laboratory study was to analyze the influence of titanium dioxide (TiO2 ) content and antagonistic material on the wear of polyetherketoneketones (PEKKs). Methods: Twenty-four disk-shaped specimens of two PEKK materials containing either 10 wt% or 20 wt% TiO2 particles (P10 and P20) were dynamically loaded in a chewing simulator with 49 N and additional thermal cycling (5–55 °C). Subgroups of 8 specimens each were loaded with spherical antagonists made from either steatite ceramic (St), zirconia (Zr), or the same PEKK material (P10 or P20). After 120, 000, 240, 000, 480, 000, 840, 000, and 1, 200, 000 loading cycles the vertical substance loss and the volume loss of the loaded specimens were evaluated using a laser scanner. Data were checked considering the normal distribution (Shapiro–Wilk test) and were inspected for significant differences by means of single factor variance analyses and post hoc pair comparison (Games-Howell test). Results: After 1, 200, 000 chewing cycles, statistical analyses revealed a significant influence of the antagonistic material. A significant difference was also found between the tested PEKKs if Zr was used as the antagonist. The volume loss ranged from between 0.073 mm 3 (P20-P20) and 0.228 mm 3 (P10-St), and the vertical substance loss ranged between 73.71 μm (P20-P20) and 115.268 μm (P10-Zr). Significance: The inclusion of TiO2 particles influences the wear behavior of PEKK materials.